The Relationship among Antibiotic Consumption, Socioeconomic Factors and Climatic Conditions. Issue 3 (2010) - Marra, Fawziah; Mak, Sunny; Chong, Mei; Patrick, David M
Abstract : BACKGROUND: Antibiotic consumption in human populations is one of the factors responsible for the emergence of resistant organisms. It is important to track population-based data on an ongoing basis, and to explore the determinants of regional variation in antibiotic consumption. METHODS: Population-level data were obtained on all outpatient oral antibiotic prescriptions dispensed within British Columbia (BC) between 1996 and 2007. Prescriptions were expressed as the defined daily dose per 1000 inhabitants. Geographical information systems mapping was used to display the spatial variations of antibiotic consumption in BC. The relationships among antibiotic consumption, socioeconomic factors and climatic conditions were explored using Pearson's correlation and regression modelling. RESULTS: Overall antibiotic consumption was highest in the northern regions of BC. Higher rates of consumption were associated with a greater proportion of the Aboriginal population, lower levels of education and individuals younger than 15 years of age. An inverse correlation was found between some classes of antibiotics and the following factors: individuals older than 65 years of age, mortality rate, doctor-to-population ratio, household size and higher July temperatures. The adjusted regression analyses indicated that higher antibiotic consumption was associated with a higher proportion of Aboriginals and household income. CONCLUSION: Different rates of antibiotic consumption exist within BC. The use of antibiotics is correlated with several socioeconomic factors and climatic conditions. It may be useful to consider these factors when designing policies to address antibiotic consumption in the community.